2021
DOI: 10.3390/mi12070831
|View full text |Cite
|
Sign up to set email alerts
|

A Miniature Four-Channel Ion Trap Array Based on Non-silicon MEMS Technology

Abstract: With the increasing application field, a higher requirement is put forward for the mass spectrometer. The reduction in size will inevitably cause a loss of precision; therefore, it is necessary to develop a high-performance miniature mass spectrometer. Based on the researches of rectangular ion trap, the relationship between mass resolution and structural parameters of the ion trap array was analyzed by further simulation. The results indicate that, considering the balance of mass resolution and extraction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In a similar size, the previously proposed miniature four-channel RIT [ 17 ] ( r x = 1.4 mm, r y = 1.61 mm of a single channel) in our laboratory optimized the proportions of high-order fields and improved the analysis performance compared with the single-channel one, but at the cost of almost quadrupled volume and higher amplitude or frequency of the RF signal. The mass resolution of miniature HreLIT in this work with a tiny size between the single-channel and four-channel RIT was the most outstanding in these three ion traps.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar size, the previously proposed miniature four-channel RIT [ 17 ] ( r x = 1.4 mm, r y = 1.61 mm of a single channel) in our laboratory optimized the proportions of high-order fields and improved the analysis performance compared with the single-channel one, but at the cost of almost quadrupled volume and higher amplitude or frequency of the RF signal. The mass resolution of miniature HreLIT in this work with a tiny size between the single-channel and four-channel RIT was the most outstanding in these three ion traps.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, a Halo ion trap [ 13 ] with a field radius of only 0.5 mm was fabricated with MEMS technology, but the low resolution was confirmed; Yu et al [ 14 ] reported an RIT with a field radius of 1.5 mm, being built by stereo lithography apparatus (SLA) and offering a slightly higher resolution of 100; Huang and co-worker [ 15 ] optimized a MEMS-based RIT by working on the relationships of ion trapping efficiency with length–width ratio and radio frequency (RF) voltage; Szyszka et al [ 16 ] combined the MEMS with 3D printing technology successfully to fabricate a miniature quadrupole mass analyzer, but this structure has lower resolution and ion capacity compared with ion traps. The miniature RIT array proposed in our laboratory [ 17 ] was prepared by MEMS technology, and the resolution could exceed 700. However, there remains much room for improvement compared with ion traps in conventional size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these methods present the ideal sensitivity and selectivity for assaying the level of GSH in human cells or tissues, the application of a fluorometric assay suffers from the difficulties caused by the necessity for the derivatization procedures of the samples before measurement, the fact that the utilization of an electrochemical detector needs an operating electrochemical cell with a higher applied oxidation potential, resulting in its shortened life span, and high-performance liquid chromatography, capillary electrophoresis, mass spectrometry, magnetic resonance spectroscopy and surface-enhanced Raman spectroscopy require the use of the expensive, sophisticated and specialized apparatus as well as the requirement for experienced technicians, which severely confines the applications of these techniques in clinical chemistry [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. Conversely, the colorimetric assay has received continuous attention as an attractive alternative strategy because it is a simple, convenient, sensitive and accurate route to accomplish the assessment.…”
Section: Introductionmentioning
confidence: 99%